A DUAL PERSPECTIVE IN LEGAL TRANSLATION - Stolze, Radegundis (Vertimo studijos, 2017)
The article describes, on the basis of hermeneutics, the specific perspective from which a translator may approach legal texts, as translation is seen as a personalized activity. Different text types are rooted in a specific legal system and fulfil their function within a special field of law, and the cultural and legal background is evident in linguistic aspects on a textual level. Comparative law carries out research on the differences in legal concepts, whereas translation studies and practice use this knowledge as a basis for work. Legal terminology has various levels of abstraction and appears in texts along with general language words. Fields of orientation for the translator are presented here, such as legal contexts, genre, concepts and style. This should be combined with proficiency in writing according to the text function, terminology and standard formulae. The translator tries to make source cultural and legal aspects transparent for target readers, as translation is always a means of comprehension that furthers communication.